The effects of genetic distance, nutrient conditions, and recognition ways on outcomes of kin recognition in Glechoma longituba - Fan, Yilei; Zhang, Ruichang; Zhang, Yuanlin; Yue, Ming (Frontiers in Plant Science, 2022)
Kin recognition might help plants decrease competitive cost and improve inclusive fitness with close genes; thus it might interact with environmental factors to affect communities. Whether and how various factors, such as the genetic distance of neighbors, environmental stressors, or the way a plant recognizes its neighbors, might modify plant growth strategies remains unclear. To answer these questions, we conducted experiments in which ramets of a clonal plant, Glechoma longituba, were grown adjacent to different genetically related neighbors (clone kin / close kin / distant kin) in different nutrient conditions (high / medium / low), or with only root exudates from pre-treatment in culture solution. By comparing competitive traits, we found that: (1) kin recognition in G. longituba was enhanced with closer genetic distance; (2) the outcomes of kin recognition were influenced by the extent of nutrient shortage; (3) kin recognition helped to alleviate the nutrient shortage effect; (4) kin recognition via root exudates affected only below-ground growth. Our results provide new insights on the potential for manipulating the outcome of kin recognition by altering neighbor genetic distance, nutrient conditions and recognition ways. Moreover, kin recognition can help plants mitigate the effects of nutrient shortage, with potential implications in agricultural research.